Justice for institutional child abuse: Comparing views from survivor and non-survivor led advocacy groups - Alasdair Henry; Katie Wright; Anthony Moran (Child Protection and Practice)
Background: How victims and survivors of non-recent institutional child abuse – and the advocacy groups that support them – conceptualise justice has become a central concern for policy makers designing redress schemes. Objectives: This study aimed to explore articulations of justice by two types of advocacy organisations in Australia – survivor and non-survivor led groups – by examining transcripts from public hearings of the Australian Royal Commission into Institutional Responses to Child Sexual Abuse. Participants and setting: Hearings held in 2015 for Case Study 25: Redress and Civil Litigation were analysed. The analysis focused on five survivor led groups and 13 non-survivor led groups. Methods: Using a framework adapted from Daly (2014, 2017), qualitative content and thematic analysis was used to analyse transcript data to identify ''justice interests'' and “survival needs”. Results: For survivor led groups, validation was the most frequently coded justice interest, while for the non-survivor led groups, the category of survival needs was the most frequently recorded element. Conclusions: Advocacy groups contribute highly valuable insights and perspectives to redress consultation and design processes. A key justice interest emphasised by survivor led groups was the need for public acknowledgement of how offending institutions wield power, both in the abuse of children and in the subsequent strategies employed to ensure survival of the institution and avoid justice processes. For non-survivor led groups, communicating their professional expertise about what victims and survivors need from a redress scheme was paramount.